2006
DOI: 10.5271/sjweh.973
|View full text |Cite
|
Sign up to set email alerts
|

Update of a meta-analysis on lung cancer and welding

Abstract: The following articles refer to this text: 2007;33(5): 379-386; 2008;34(6):444-450

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
54
3
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 74 publications
8
54
3
3
Order By: Relevance
“…This finding is consistent with that of a Swedish study that indicated that welders exposed to high levels of chromium have a higher risk for cancer of the trachea, bronchus, and lung than welders exposed to low levels of chromium (2, 3) and those of several other studies (26). Furthermore, the finding is biologically highly plausible (25), and the association did not disappear when smoking and asbestos exposure was adjusted for in the survival analysis (6,18,22). To test the hypothesis of higher risk for stainless steel welders, it seemed the most sensible to compare all welders that had been welding with stainless steel alloys, with only mild steel welders, even though many stainless steel welders were also mild steel welders.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This finding is consistent with that of a Swedish study that indicated that welders exposed to high levels of chromium have a higher risk for cancer of the trachea, bronchus, and lung than welders exposed to low levels of chromium (2, 3) and those of several other studies (26). Furthermore, the finding is biologically highly plausible (25), and the association did not disappear when smoking and asbestos exposure was adjusted for in the survival analysis (6,18,22). To test the hypothesis of higher risk for stainless steel welders, it seemed the most sensible to compare all welders that had been welding with stainless steel alloys, with only mild steel welders, even though many stainless steel welders were also mild steel welders.…”
Section: Discussionsupporting
confidence: 82%
“…The increased risk of lung cancer among mild steel welders is consistent with those found in a large number of earlier studies summarized in meta-analyses with updates (4,18,22). Earlier studies have found no clear indications that the risk is related to various measures of welding exposure (18).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Interestingly, more recent occupational studies of welders overlook iron oxide, focusing on other workplace hazards such as asbestos, hexavalent chromium, and manganese [30]. The lung effects including carcinogenicity of welding fumes have been reviewed in depth and current evidence points to co-exposure with known carcinogens (i.e., asbestos, Cr, Mg, Ni) as a possible explanation for elevated cancer risk [26,31].…”
Section: Occupational Inhalation Exposure To Iron Oxide Particlesmentioning
confidence: 99%